The impacts of political stability, renewable energy consumption, and economic growth on tourism in Turkey: New evidence from Fourier Bootstrap ARDL approach. (May 2022) - Aydin, Mucahit
Abstract: The study investigates the impacts of political stability, renewable energy consumption, and economic growth on tourism in Turkey for the period 1996–2018. For this purpose, we used a cointegration test, long-run estimator, and causality test that account smooth structural breaks for the robust results. The results showed that the cointegration relationship is valid for the model in which tourism is the dependent variable. According to the long-run estimates, political stability and renewable energy consumption have a significant and positive impact on tourism. The causality test results confirm unidirectional causality from renewable energy consumption and political stability to tourism and from tourism to economic growth. The results, therefore, highlight the necessity of implementing environmentally-friendly tourism policies and maintain political stability. The comprehensive results of this study provide a guide for policymakers. Graphical abstract: Image 1